2013
DOI: 10.1097/mpa.0b013e318288360a
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status and Oxidative Stress Markers in Pancreatic Cancer and Chronic Pancreatitis

Abstract: Reduced antioxidant defense system capacity and increased markers of oxidative stress were found in PC and CP. PON1-L and CAT activities, along with ox-LDL/LDL levels, were the independent factors differentiating the patients with PC from the patients with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 41 publications
0
54
1
2
Order By: Relevance
“…Approximately 95% of all PDA show acquisition of a Kras mutation (Hruban et al, 2001) and many of these tumors also have increased cellular oxidative stress levels (Kodydkova et al, 2013), as confirmed by staining for protein adducts formed from ROS-generated reactive lipids such as 4-hydroxy-2-nonenal (4HNE) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Approximately 95% of all PDA show acquisition of a Kras mutation (Hruban et al, 2001) and many of these tumors also have increased cellular oxidative stress levels (Kodydkova et al, 2013), as confirmed by staining for protein adducts formed from ROS-generated reactive lipids such as 4-hydroxy-2-nonenal (4HNE) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
“…The resulting presence of high levels of hydrogen peroxide correlated with an increase in oxidized low density lipoproteins (LDL) (Kodydkova et al, 2013). Analyses of tissue samples from p48 cre ;LSL-Kras G12D mice indicate that ROS already are induced in acinar cells and gradually-increased during ADM and PanIN formation and progression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have high impact on physiological and pathological status by inducing oxidative stress mediated inflammatory response in several tissues [5]. Increased status of ROS is also an important factor to develop colitis associated colon cancer [6] and it becomes into oxyradical overload disorder [7]. Oxidative stress in colonic mucosa was counter balanced through endogenous anti-oxidant defense portal systems including superoxide dismutase, catalase and glutathione peroxidase myeloperoxidase to decompose ROS which generate in response to inflammatory stimuli [8].…”
Section: Introductionmentioning
confidence: 99%
“…TAC has been reported to be decreased in cancer patients (32); TAC is thus considered to be a significant marker for diagnosing cancers of the lung (33), breast (34,35), stomach (36), colon (37), and Barrett's esophagus (38). Although reduced antioxidant capacity has been noted in pancreatic cancer, this has not been observed in ampullary cancer, IPMN, or CCA (39).…”
Section: Introductionmentioning
confidence: 97%